Synthesis of Novel Composites of HCl-Doped Polyaniline with Maize, Rice and Wheat Flour - Kanwal, Farah; Rehman, Rabia; Batool, Aisha; Saeed, Muhammad (Asian Journal of Chemistry, 2013)
Polyaniline and its composites with rice, maize and wheat flour were prepared at 0 and -5 ºC by oxidative polymerization of aniline in the presence of potassium dichromate as an oxidizing agent. The prepared composites were characterized by fourier transform infrared spectroscopy, UV-visible spectroscopy and standard four probe method. The UV-visible spectroscopy of the polyaniline composites show absorption maxima due to p-p* transition of the benzenoid ring and charge transfer excitations of the quinonoid structure, which are characteristics of emeraldine base. FT-IR spectra of the polyaniline composites is similar to that of pure polyaniline but with the shifts of bands to higher wave numbers due to strong interaction of dopants and polyaniline matrix. The conductivity measurements revealed that the conductance of polyaniline-maize composites offer better conducting properties among all samples.